Metabolites-Enabled Survival of Crucian Carps Infected by Edwardsiella tarda in High Water Temperature - Jiang, Ming; Chen, Zhuang-gui; Zheng, Jun; Peng, Bo (Frontiers in Immunology, 2019)
Temperature is one of the major climate factors that affects the outbreak of infectious disease. Lines of evidences have shown that virulence factors can be controlled by thermo-sensors in bacterial pathogens. However, how temperature influence host’s responses to the pathogen is still largely unexplored, and the study on which might pave the way to develop strategies to manage pathogenic bacterial infection. In the present study, we show that finfish Carassius carassius, the crucian carp that is tolerant to a wide range of temperature, is less susceptible to bacterial infection when grown in 20 ℃ than in 30 ℃. This differential response of C. carassius to bacterial infection could be partially explained by the different metabolisms under those respective temperatures, where C. carassius shows elevated tricarboxylic acid cycle (TCA cycle) but decreased taurine and hypotaurine metabolism as well as lower biosynthesis of unsaturated fatty acids. The decreased abundance of palmitate, threonine, and taurine represents the most characteristic metabolic feature. Consistently, exogenous palmitate, threonine or taurine enhanced the survival of C. carassius to bacterial infection at 30 ℃ in a dose-dependent manner. This effect could be attributed to the inhibition on the TCA cycle by the three metabolites. This notion is further supported by the fact that low concentration of malonate, a succinate dehydrogenase inhibitor, increases the survival of C. carassius at 30 0C as well. On the other hand, addition of the three metabolites rescued the decreased expression of pro-inflammatory cytokines including TNF-α1, TNF-α2, IL-1β1, IL-1β2, and lysozyme at 30 0C. Taken together, our results revealed an unexpected relationship between temperature and metabolism that orchestrates the immune regulation to bacterial pathogens. Thus, this study shed light on the modulation of finfish physiology to fight against bacterial infection through metabolism.